Fiber Bragg grating wavelength drift in long-term high temperature annealing - Grobnic, Dan; Hnatovsky, Cyril; Dedyulin, Sergey; Walker, Robert B; Ding, Huimin; Mihailov, Stephen J (Sensors (Basel, Switzerland), 2021)
High-temperature-resistant fiber Bragg gratings (FBGs) are the main competitors to thermocouples as sensors in applications for high temperature environments defined as being in the 600–1200 °C temperature range. Due to their small size, capacity to be multiplexed into high density distributed sensor arrays and survivability in extreme ambient temperatures, they could provide the essential sensing support that is needed in high temperature processes. While capable of providing reliable sensing information in the short term, their long-term functionality is affected by the drift of the characteristic Bragg wavelength or resonance that is used to derive the temperature. A number of physical processes have been proposed as the cause of the high temperature wavelength drift but there is yet no credible description of this process. In this paper we review the literature related to the long-term wavelength drift of FBGs at high temperature and provide our recent results of more than 4000 h of high temperature testing in the 900–1000 °C range. We identify the major components of the high temperature wavelength drift and we propose mechanisms that could be causing them.